البحر: الفضاء و دينامية الحضور في رواية خويا دحمان لمرزاق بقطاش - جوادي هنية (Université de M'sila, 2021)
تتناول الدراسة الحضور الدّينامي لفضاء البحر في رواية خويا دحمان للكاتب الجزائري مرزاق بقطاش، وتسعى إلى إبراز تقاطعاته مع مكوّنات الرّواية، وكشف تأثيراته في شخصية البطل، وكيف حفر فيها وأضْفي عليها من صفاته وخصائصه، وقد بَدا البحر في الرواية فضاء خصبا، يمدّ المتخيّل بما لا حدود له من الموضوعات والرموز. يعزّز حضورَه الفعَّال، تدفقُ تيّار الوعي، وتوظيف المنولوج الدّاخلي، وأسلوب المناجاة، والاسترجاع، والحلم... وهي من أهم الأساليب التي جعلت منه فضاء يزخر بالدّلالة: الوجودية والتّاريخية والاجتماعية والأيديولوجية والنّفسية والفنيّة في الرواية موضوع الدراسة. Abstract : The study deals with the dynamic presence of the sea space in the novel by Khoya Dahmane by the Algerian writer Merzak Bakttache, and seeks to highlight its intersections with the components of the novel, and reveal its effects on the character of the hero, and how he engraved in it and gave it his qualities and characteristics. It has limits from themes and icons. Its active presence enhances the flow of the stream of consciousness, employing the inner view, the method of communion, retrieval, and dreaming ... which are among the most important methods that made it a space full of significance: existential, historical, social, ideological, psychological and artistic in the novel. :
Keywords: الرواية ; البحر ; البطل ; التداعي ; الدلالة ; novel ; sea ; hero ; monologue ; significanc